The Effect of Social Distance on Intertemporal Choice of Reward Processing: An Event-Related Potentials Study - Tang, Shulin; Guo, Jie; Li, Bing; Song, Zhikai (Frontiers in Human Neuroscience, 2021)
Social factors can affect the processing of intertemporal choice, but the influence of social distance on the rewarding process of intertemporal choice is unclear. Therefore, by designing a novel cognitive resource competition paradigm for undifferentiated intertemporal choice, this article aims to explore the influence of social distance on intertemporal choice reward processing at the electrophysiological level. It was found that compared with stranger, P3a is greater for friend, which means social distance is evaluated in the early stage. In addition, different brain regions in the early stages are taking charge of processing the soon-but-small (SS) and later-but-lager (LL) reward in intertemporal choice. There is an interaction effect between social distance (friend vs. stranger) and intertemporal choice (SS reward vs. LL reward) on P3b. Under friend condition, the P3b induced by LL reward is more positive than SS reward. Under the condition of choosing the LL reward, the P3b induced by friend is more positive than stranger. This result shows that in the latter stage of reward processing, the evaluation process of time discounting is less sensitive in LL reward for friend caused by lack of cognitive resources which is occupied when dealing with social distance in advance, and thus the degree of time discount was reduced. These findings demonstrate that P3b is the key index of time discounting and immediate and delayed rewards are valued in different brain regions.